Rubber dam composite material with excellent air tightness and long service life and preparation method thereof

By using specific combinations of materials and processes in the preparation of rubber dam composite materials, the existing rubber dam lacks airtightness and poor aging resistance are solved, and rubber dam composite materials with excellent airtightness and long life are achieved. Significantly improves service life and safety.

CN119391095AActive Publication Date: 2025-02-07SHANDONG CHAMBROAD SINOPOLY NEW MATERIAL CO LTD

Patent Information

Application Number
CN202411517196.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-02-07
Estimated Expiration
2044-10-29

AI Technical Summary

Technical Problem

The existing rubber dam has poor gas/water tightness, resulting in insufficient gas-retaining performance, reduced dam height, reduced water barrier performance, and even safety hazards. At the same time, the aging resistance of natural rubber is poor, and anti-aging agents are needed to waste resources.

Method used

Raw glue, reinforcement filler, activator, plasticizer, magnesium oxide, promoter, vulcanizer and specific types of adhesives (such as super tackifying resin Koresin and modified phenolic resin B-16S) as preparation materials , rubber dam composite materials with excellent airtightness and long life are prepared through kneading and vulcanization processes.

Benefits of technology

It significantly improves the airtightness, aging resistance and UV resistance of the rubber dam, enhances the adhesion between different rubber layers, extends the service life, and ensures the gas-safety and safety of the rubber dam.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005107041120000071
    Figure BDA0005107041120000071
Patent Text Reader

Abstract

The invention provides a rubber dam composite material with excellent air tightness and long service life. The rubber dam composite material is prepared from the following components in parts by weight: 100 parts of raw rubber, 40-100 parts of a reinforcing filler, 2-15 parts of an activating agent, 4-30 parts of a plasticizer, 0-10 parts of magnesium oxide, 1.0-10.0 parts of an accelerant, 0.5-10 parts of a vulcanizing agent and 0.5-10 parts of an adhesive, the raw rubber comprises butyl rubber and a second rubber component in a mass ratio of (10-90): (10-90), and the second rubber component is ethylene propylene diene monomer and / or natural rubber; the adhesive is selected from tackifying resin and modified phenolic resin. The rubber dam composite material has excellent aging resistance and ultraviolet resistance under the combined action of the raw materials of specific types and dosages, and the bonding performance between different rubber layers (or and between the different rubber layers and polyester or chinlon impregnated canvas) is excellent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of rubber composite materials, and in particular relates to a rubber dam composite material with excellent air tightness and long service life and a preparation method thereof. Background Art

[0002] Rubber dam, also known as rubber sluice, is a bag-type water retaining dam made of high-strength synthetic fiber fabric as a load-bearing skeleton, coated with rubber inside and outside as a protective layer, processed into rubber tape, and then anchored on the bottom plate to form a closed dam bag, which is inflated with water (air) through the filling and discharge pipeline. Rubber dams are divided into two types: water-filled and air-filled. The dam top can overflow, and the dam height can be adjusted as needed to control the upstream water level, so as to play the role of irrigation, power generation, shipping, flood control, tide prevention and other benefits.

[0003] The main raw materials used in existing rubber dams are EPDM and natural rubber. Due to the poor air / water tightness of the material itself, the air retention performance of the rubber dam is insufficient, which causes the dam height to drop, resulting in reduced water-blocking performance or no water-blocking effect, and even creates safety hazards. Therefore, it is necessary to check the air pressure from time to time; on the other hand, due to the poor aging resistance of natural rubber, a certain amount of antioxidant needs to be added during the production process to improve the aging resistance of the rubber dam, wasting a lot of manpower, material and financial resources. Summary of the invention

[0004] In view of this, the object of the present invention is to provide a rubber dam composite material with excellent air tightness and long life and a preparation method thereof. The rubber dam composite material has excellent aging resistance and UV resistance, and excellent bonding performance between different rubber layers (or with polyester or nylon dipped canvas).

[0005] The present invention provides a rubber dam composite material with excellent air tightness and long service life, and the raw materials for preparing the composite material include the following components:

[0006] 100 parts of raw rubber, 40-100 parts of reinforcing filler, 2-15 parts of activator, 4-30 parts of plasticizer, 0-10 parts of magnesium oxide, 1.0-10.0 parts of accelerator, 0.5-10 parts of vulcanizer and 0.5-10.0 parts of adhesive;

[0007] The raw rubber comprises a butyl rubber and a second rubber component in a mass ratio of (10-90):(10-90), wherein the second rubber component is EPDM rubber and / or natural rubber;

[0008] The adhesive is selected from tackifying resins and modified phenolic resins.

[0009] Preferably, the tackifying resin is super tackifying resin Koresin;

[0010] The modified phenolic resin is modified resorcinol formaldehyde resin B-16S.

[0011] Preferably, the reinforcing filler is selected from one or more of carbon black, pyrolysis carbon black, calcium carbonate, calcium sulfate, dolomite powder, clay, clay, montmorillonite, clay, barium sulfate, talc, magnesium carbonate, white carbon black, magnesium silicate, graphene and cellulose bio-based.

[0012] Preferably, the activator is selected from one or more of zinc oxide, stearic acid, lead oxide and titanium dioxide;

[0013] The plasticizer is selected from one or more of naphthenic oil, aromatic oil, paraffin oil, butyl oleate and dibutyl phthalate;

[0014] The accelerator is selected from one or more of thiazole accelerators, thiuram accelerators, dithiocarbamate accelerators, xanthate accelerators, guanidine accelerators, aldehyde amine accelerators, sulfenamide accelerators and thiourea accelerators;

[0015] The vulcanizing agent is selected from sulfur and / or peroxide.

[0016] The present invention provides a method for preparing the rubber dam composite material with excellent air tightness and long service life as described in the above technical solution, comprising the following steps:

[0017] The raw rubber is mixed, and reinforcing fillers, adhesives, magnesium oxide and plasticizers are added and mixed continuously. When the temperature reaches 110-150°C, the rubber is discharged to obtain a masterbatch;

[0018] The first stage masterbatch is cooled and then placed aside, and then mixed with a vulcanizing agent, an accelerator, and an activator for further mixing, and when the temperature reaches 90 to 130° C., the masterbatch is discharged to obtain a second stage final mix;

[0019] The second stage final mixing rubber is sheeted and then parked to obtain a rubber dam composite material.

[0020] Preferably, the raw rubber includes natural rubber, and the natural rubber is masticated before use until the Mooney viscosity ML(1+4)100 value is 40-70.

[0021] Preferably, reinforcing filler, adhesive, magnesium oxide and plasticizer are added and kneading is continued at 40-80° C. for 4-8 minutes;

[0022] The temperature of the masterbatch cooling is lower than 80°C, and the storage time is greater than 30 minutes;

[0023] Then mix with the vulcanizing agent, accelerator and activator and continue kneading for 1 to 3 minutes;

[0024] The temperature of the second stage final mixing after the sheet is unrolled is 20-30° C. and the time is 18-24 hours.

[0025] Preferably, the vulcanization temperature is 130-180° C., the vulcanization pressure is 20-40 tons, and the vulcanization time is 5-60 minutes.

[0026] The present invention provides a rubber dam composite material with excellent air tightness and long life, and the raw materials for preparation include the following components: 100 parts of raw rubber, 40-100 parts of reinforcing filler, 2-15 parts of activator, 4-30 parts of plasticizer, 0-10 parts of magnesium oxide, 1.0-10.0 parts of accelerator, 0.5-10 parts of vulcanizer and 0.5-10.0 parts of adhesive; the raw rubber includes butyl rubber and a second rubber component in a mass ratio of (10-90): (10-90), and the second rubber component is ethylene propylene diene monomer rubber and / or natural rubber; the adhesive is selected from tackifying resin and modified phenolic resin. Under the joint action of the above-mentioned specific types and amounts of raw materials, the above-mentioned rubber dam composite material has excellent aging resistance and UV resistance, and excellent bonding performance between different adhesive layers (or with polyester or nylon dipped canvas). DETAILED DESCRIPTION

[0027] The present invention provides a rubber dam composite material with excellent air tightness and long service life, and the raw materials for preparing the composite material include the following components:

[0028] 100 parts of raw rubber, 40-100 parts of reinforcing filler, 2-15 parts of activator, 4-30 parts of plasticizer, 0-10 parts of magnesium oxide, 1.0-10.0 parts of accelerator, 0.5-10 parts of vulcanizer and 0.5-10.0 parts of adhesive;

[0029] The raw rubber comprises a butyl rubber and a second rubber component in a mass ratio of (10-90):(10-90), wherein the second rubber component is EPDM rubber and / or natural rubber;

[0030] The adhesive is a tackifying resin and a modified phenolic resin.

[0031] In order to make the rubber dam composite material have excellent air retention performance, aging resistance, ozone resistance and ultraviolet resistance, the present invention adopts butyl rubber and uses or replaces part of EPDM (or natural rubber); however, after the introduction of butyl rubber, the interlayer adhesion between butyl rubber and other rubber dams is slightly poor. In this regard, the present invention solves the problem of limiting the application of butyl rubber in rubber dams and air shield dams by introducing a specific type of adhesive, that is, without affecting the interlayer adhesion, the air and water retention performance of the rubber dam is greatly improved, which has very important economic significance for realizing the application of butyl rubber in rubber dams.

[0032] The raw materials for preparing the composite material provided by the present invention include 100 parts of raw rubber; the raw rubber includes butyl rubber and a second rubber component in a mass ratio of (10-90): (10-90), and the second rubber component is EPDM rubber and / or natural rubber. In the present invention, the butyl rubber is selected from one or more of ordinary butyl rubber, brominated butyl rubber, chlorinated butyl rubber, star-branched butyl rubber and halogenated butyl rubber, preferably brominated butyl rubber. The second rubber component is EPDM rubber and / or natural rubber.

[0033] The raw materials for preparing the composite material provided by the present invention include 40 to 100 parts of a reinforcing filler; the reinforcing filler is selected from one or more of carbon black, pyrolysis carbon black, calcium carbonate, calcium sulfate, dolomite powder, clay, clay, montmorillonite, clay, barium sulfate, talcum powder, magnesium carbonate, white carbon black, magnesium silicate, graphene and cellulose bio-based.

[0034] The raw materials for preparing the composite material provided by the present invention include 2 to 15 parts of an activator, wherein the activator is selected from one or more of zinc oxide, stearic acid, lead oxide and titanium dioxide;

[0035] The raw materials for preparing the composite material provided by the present invention include 4 to 30 parts of a plasticizer, wherein the plasticizer is selected from one or more of naphthenic oil, aromatic oil, paraffin oil, butyl oleate, and dibutyl phthalate;

[0036] The raw materials for preparing the composite material provided by the invention include 0 to 10 parts of magnesium oxide.

[0037] The raw materials for preparing the composite material provided by the present invention include 1.0 to 10.0 parts of an accelerator, wherein the accelerator is selected from one or more of thiazole accelerators, thiuram accelerators, dithiocarbamate accelerators, xanthate accelerators, guanidine accelerators, aldehyde amine accelerators, sulfonamide accelerators and thiourea accelerators.

[0038] The raw materials for preparing the composite material provided by the invention include 0.5 to 10 parts of a vulcanizing agent; the vulcanizing agent is selected from sulfur and / or peroxide.

[0039] The raw materials for preparing the composite material provided by the present invention include 0.5 to 10.0 parts of an adhesive, wherein the adhesive is selected from a tackifying resin and a modified phenolic resin; the tackifying resin is selected from a super tackifying resin Koresin; the modified phenolic resin is selected from a modified resorcinol formaldehyde resin B-16S; and the mass ratio of the tackifying resin to the modified phenolic resin is 0.5 to 10:0.5 to 8. By selecting the above-mentioned specific type of modified phenolic resin adhesive, the present invention improves the bonding performance between butyl rubber and other rubbers (as well as polyester or nylon dipped canvas), prolongs the service life, and ensures the gas retention, aging resistance, ozone resistance and UV resistance of the rubber dam.

[0040] The present invention provides a method for preparing a composite material of a rubber dam and an air shield dam having excellent air tightness and long service life as described in the above technical solution, comprising the following steps:

[0041] The raw rubber is mixed, and reinforcing fillers, adhesives, magnesium oxide and plasticizers are added and mixed continuously. When the temperature reaches 110-150°C, the rubber is discharged to obtain a masterbatch;

[0042] The first stage masterbatch is cooled and then placed aside, and then mixed with a vulcanizing agent, an accelerator, and an activator for further mixing, and when the temperature reaches 90 to 130° C., the masterbatch is discharged to obtain a second stage final mix;

[0043] The second stage final mixing rubber is sheeted and then parked to obtain a rubber dam composite material.

[0044] The method provided by the invention has simple process, low requirements on equipment, and excellent processing performance, and is suitable for wide use.

[0045] The method comprises mixing raw rubber, adding reinforcing filler, adhesive, magnesium oxide and plasticizer and continuing to mix, and when the temperature reaches 110-150° C., the rubber is discharged to obtain a masterbatch. The method comprises adding raw rubber to an internal mixer and mixing for 25-35 seconds, then adding reinforcing filler, adhesive, magnesium oxide and plasticizer; adding reinforcing filler, adhesive, magnesium oxide and plasticizer and continuing to mix at 40-80° C. for 4-8 minutes.

[0046] The raw rubber in the present invention includes natural rubber, which is masticated before use until the Mooney viscosity ML (1+4) 100 value is 40 to 70. In the present invention, the natural rubber is preferably masticated for 2 to 20 times, and the roller temperature is controlled at 50 to 70°C.

[0047] After obtaining a masterbatch, the masterbatch is cooled and then parked, and then mixed with a vulcanizing agent, an accelerator, and an activator for continuous banburying. When the temperature reaches 90 to 130° C., the masterbatch is discharged to obtain a second stage final mixing. The masterbatch is cooled to a temperature lower than 80° C., and the parking time is greater than 30 minutes. In the present invention, the time for continuing banburying with a vulcanizing agent, an accelerator, and an activator is 1 to 3 minutes.

[0048] After obtaining the second-stage final rubber mix, the second-stage final rubber mix is ​​cut into sheets and then parked to obtain a rubber dam composite material. The temperature of the second-stage final rubber mix after being cut into sheets in the present invention is 20 to 30° C. and the time is 18 to 24 hours. The present invention vulcanizes the mixed rubber, i.e., the rubber dam composite material, and performs relevant physical and mechanical property tests.

[0049] The rubber dam composite material prepared by the above process of the present invention adopts butyl rubber, which has good air tightness and can be used in rubber dams to greatly improve its gas retention performance; using its lower unsaturation, the rubber dam composite material has excellent aging resistance and UV resistance, which can fully meet the use environment of the rubber dam. The present invention adopts and uses a specific type of adhesive to greatly improve the gas retention performance of the rubber dam without affecting the interlayer bonding, which has very important economic significance for realizing the application of butyl rubber in rubber dams.

[0050] In order to further illustrate the present invention, a rubber dam composite material with excellent air tightness and long life and a preparation method thereof provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0051] In the following embodiments, halogenated butyl rubber: a product of Shandong Jingbo Zhongju New Materials Co., Ltd., preferably brominated butyl rubber; natural rubber and EPDM rubber: commercially available brands; other raw and auxiliary materials are all commercially available products.

[0052] Example 1

[0053] A rubber dam composite material with excellent air tightness and long service life comprises the following components, measured by mass: 60 parts of brominated butyl rubber, 20 parts of EPDM, 20 parts of natural rubber, 60 parts of carbon black, 30 parts of calcium carbonate, 1.0 part of magnesium oxide, 10 parts of zinc oxide, 15 parts of paraffin oil, 2 parts of Koresin, 1 part of B-16S, 1.5 parts of sulfur, 1 part of accelerator DM, 1.5 parts of accelerator CZ, 2 parts of diisopropyl peroxide (DCP), and 1 part of triallyl isocyanurate (TAIC).

[0054] The steps of the preparation method of the rubber dam composite material with excellent air tightness and long service life are as follows:

[0055] 1) First, the natural rubber is thinly plasticized on an open mill and left for 8 hours to make plasticized rubber;

[0056] 2) Add bromobutyl rubber, EPDM rubber, and plasticized rubber in sequence, mix for 1 minute, then add carbon black, calcium carbonate, magnesium oxide, and adhesive in sequence, mix for 2 minutes, then add plasticizer and mix, when the temperature in the internal mixer reaches 130°C, discharge the rubber to obtain a masterbatch;

[0057] 3) After the first stage of the masterbatch in step 2) is cooled and left for more than 2 hours, the masterbatch, activator, vulcanizer, accelerator, etc. are put into an internal mixer and continue to be mixed. When the temperature in the internal mixer reaches 110° C., the masterbatch is discharged to obtain the second stage final mix.

[0058] 4) The mixture was thinned on an open mill for 6 times, rolled off with a roller distance of 2 mm, and left to stand at a temperature of 20 to 30° C. for 18 hours to obtain a mixed rubber, i.e., a rubber dam composite material.

[0059] 5) The mixed rubber obtained in step 4) is tested for vulcanization characteristics using a rotorless vulcanizer, and a vulcanized rubber sample is obtained using a flat plate vulcanizer to perform relevant physical and mechanical property tests.

[0060] The vulcanization temperature in step 5) is 160°C.

[0061] Example 2

[0062] A rubber dam composite material with excellent air tightness and long service life comprises the following raw materials, measured by mass: 60 parts of brominated butyl rubber, 40 parts of EPDM rubber, 60 parts of carbon black, 30 parts of calcium carbonate, 1 part of magnesium oxide, 8 parts of zinc oxide, 15 parts of paraffin oil, 2 parts of Koresin, 1 part of B-16S, 1.5 parts of sulfur, 1 part of accelerator DM, 1.5 parts of accelerator CZ, 2 parts of diisopropyl peroxide (DCP), and 1 part of triallyl isocyanurate (TAIC).

[0063] The rubber dam composite material was prepared according to the same preparation method as in Example 1.

[0064] Comparative Example 1

[0065] A composite material for a rubber dam and an air shield dam with excellent air tightness and long service life, comprising the following raw materials, measured by mass: 100 parts of EPDM rubber, 60 parts of carbon black, 30 parts of calcium carbonate, 10 parts of zinc oxide, 15 parts of paraffin oil, 1.5 parts of sulfur, 1 part of accelerator NS, 1.5 parts of accelerator CZ, 6 parts of diisopropylbenzene peroxide (DCP), and 2 parts of triallyl isocyanurate (TAIC).

[0066] The rubber dam composite material was prepared according to the same preparation method as in Example 1.

[0067] Comparative Example 2

[0068] A rubber dam composite material with excellent air tightness and long service life, comprising the following raw materials, measured by mass: 40 parts of natural rubber, 60 parts of EPDM rubber, 60 parts of carbon black, 30 parts of calcium carbonate, 6 parts of zinc oxide, 15 parts of paraffin oil, 1.5 parts of sulfur, 1 part of accelerator NS, 1.5 parts of accelerator CZ, 6 parts of diisopropylbenzene peroxide (DCP), and 2 parts of triallyl isocyanurate (TAIC).

[0069] The rubber dam composite material was prepared according to the same preparation method as in Example 1.

[0070] Comparative Example 3

[0071] A rubber dam composite material with excellent air tightness and long service life comprises the following raw materials, measured by mass: 60 parts of brominated butyl rubber, 40 parts of EPDM rubber, 60 parts of carbon black, 30 parts of calcium carbonate, 1 part of magnesium oxide, 10 parts of zinc oxide, 15 parts of plasticizer, 1.2 parts of resorcinol, 3 parts of white carbon black, 3 parts of RA65, 1.5 parts of sulfur, 1 part of accelerator DM, 1.5 parts of accelerator CZ, 2 parts of diisopropyl peroxide (DCP) and 1 part of triallyl isocyanurate (TAIC).

[0072] The rubber dam composite material was prepared according to the same preparation method as in Example 1.

[0073] The present invention performs performance tests on the composite materials prepared in the examples and comparative examples, and the results are shown in Table 1:

[0074] Table 1 Performance test results of rubber dam composite materials of embodiments and comparative examples

[0075]

[0076] It can be seen from Examples 1 to 2 and Comparative Examples 1 to 3 that the permeability coefficient of the rubber dam composite material prepared in the embodiment of the present invention is reduced, the elongation at break is excellent, and the tensile strength of the product is greater than 12MPA, which exceeds the industry standard and meets the use requirements, indicating that it is feasible to improve the gas retention performance of the rubber dam by using butyl rubber; at the same time, the aging performance of the rubber dam composite material made of butyl rubber is improved, and the ozone aging performance remains unchanged, which helps to extend the service life of the rubber dam and achieve the purpose of reducing carbon emissions. By comparing Examples 1 to 2 and Comparative Example 3, a specific super tackifying resin Koresin and a modified resorcinol formaldehyde resin B-16S are selected as adhesives, and the interlayer adhesion of the vulcanized rubber is much higher than that of the meta-formaldehyde tackifying system, and the adhesion also exceeds that of Comparative Examples 1 to 2, indicating that the preferred tackifier of the present invention is effective. The present invention partially replaces the natural rubber and EPDM rubber in the traditional formula with butyl rubber, thereby improving the processing performance of EPDM rubber, enhancing the air retention performance of the rubber dam, and helping to further improve the comprehensive performance of the rubber. The specially selected adhesive improves the adhesion problem of butyl rubber, provides beneficial technical support for the selection of raw materials for the rubber dam, and has broad market prospects.

[0077] As can be seen from the above embodiments, the present invention provides a rubber dam composite material with excellent air tightness and long life, and the raw materials for preparation include the following components: 100 parts of raw rubber, 40-100 parts of reinforcing filler, 2-15 parts of activator, 4-30 parts of plasticizer, 0-10 parts of magnesium oxide, 1.0-10.0 parts of accelerator, 0.5-10 parts of vulcanizer and 0.5-10.0 parts of adhesive; the raw rubber includes butyl rubber and a second rubber component in a mass ratio of (10-90): (10-90), and the second rubber component is ethylene propylene diene monomer rubber and / or natural rubber; the adhesive is selected from tackifying resin and modified phenolic resin. Under the joint action of the above-mentioned specific types and amounts of raw materials, the above-mentioned rubber dam composite material has excellent aging resistance and UV resistance, and excellent bonding performance between different adhesive layers (or with polyester or nylon dipped canvas).

[0078] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A rubber dam composite material with excellent air tightness and long life, the raw materials for preparation include the following components: 100 parts of raw rubber, 40-100 parts of reinforcing filler, 2-15 parts of activator, 4-30 parts of plasticizer, 0-10 parts of magnesium oxide, 1.0-10.0 parts of accelerator, 0.5-10 parts of vulcanizer and 0.5-10.0 parts of adhesive; The raw rubber comprises a butyl rubber and a second rubber component in a mass ratio of (10-90):(10-90), wherein the second rubber component is EPDM rubber and / or natural rubber; The adhesive is selected from tackifying resins and modified phenolic resins.

2. The rubber dam composite material with excellent air tightness and long service life according to claim 1, characterized in that: The tackifying resin is a super tackifying resin Koresin; The modified phenolic resin is modified resorcinol formaldehyde resin B-16S.

3. The rubber dam composite material with excellent air tightness and long service life according to claim 1, characterized in that: The reinforcing filler is selected from one or more of carbon black, pyrolysis carbon black, calcium carbonate, calcium sulfate, dolomite powder, clay, clay, montmorillonite, clay, barium sulfate, talc, magnesium carbonate, white carbon black, magnesium silicate, graphene and cellulose bio-based.

4. The rubber dam composite material with excellent air tightness and long service life according to claim 1, characterized in that: The activator is selected from one or more of zinc oxide, stearic acid, lead oxide and titanium dioxide; The plasticizer is selected from one or more of naphthenic oil, aromatic oil, paraffin oil, butyl oleate and dibutyl phthalate.

5. The rubber dam composite material with excellent air tightness and long service life according to claim 1, characterized in that: The accelerator is selected from one or more of thiazole accelerators, thiuram accelerators, dithiocarbamate accelerators, xanthate accelerators, guanidine accelerators, aldehyde amine accelerators, sulfenamide accelerators and thiourea accelerators; The vulcanizing agent is selected from sulfur and / or peroxide.

6. A method for preparing the rubber dam composite material with excellent air tightness and long service life as claimed in claim 1, comprising the following steps: The raw rubber is mixed, and a reinforcing filler, an adhesive, magnesium oxide and a plasticizer are added and the mixing is continued. When the temperature reaches 110-150° C., the rubber is discharged to obtain a masterbatch; the adhesive is selected from a tackifying resin and a modified phenolic resin; The first stage masterbatch is cooled and then placed aside, and then mixed with a vulcanizing agent, an accelerator, and an activator for further mixing, and when the temperature reaches 90 to 130° C., the masterbatch is discharged to obtain a second stage final mix; The second-stage final rubber mixing is sheeted, parked, and vulcanized to obtain a rubber dam composite material.

7. The preparation method according to claim 6, characterized in that: The raw rubber includes natural rubber, and the natural rubber is plasticized before use until the Mooney viscosity ML (1+4) 100 value is 40-70.

8. The preparation method according to claim 6, characterized in that: Add reinforcing filler, adhesive, magnesium oxide and plasticizer and continue mixing at 40-80°C for 4-8 minutes; The temperature of the masterbatch cooling is lower than 80°C, and the storage time is greater than 30 minutes; Then mix with the vulcanizing agent, accelerator and activator and continue kneading for 1 to 3 minutes; The temperature of the second stage final mixing after the sheet is unrolled is 20-30° C. and the time is 18-24 hours.

9. The preparation method according to claim 6, characterized in that: The vulcanization temperature is 130-180°C, the vulcanization pressure is 20-40 tons, and the time is 5-60 minutes.

Citation Information

Patent Citations

  • High-gas-preservation easy bonding shaping low-cost tire airtightness layer glue composition

    CN108384130A

  • Inner liner compound for aircraft tire and preparation method

    CN110240764A

  • Graphene-containing aircraft tire sealing layer rubber material and preparation method thereof

    CN110862623A

  • Sealing adhesive tape as well as preparation method and application thereof

    CN112961622A

  • Low-temperature-resistant aging-resistant rubber material and preparation method thereof

    CN113150401A

Cited By

  • A strong adhesion gate water seal material based on ethylene-propylene rubber and a preparation method thereof

    CN122647825A